(untitled) (International relations and international law Journal, 2026)
The article provides a comprehensive assessment of Kazakhstani scholarly publications on climate change, water security, and sustainable development, viewed through the lens of climate security in Central Asia. The study covers roughly three decades, from the mid-1990s to 2024, and examines 200 articles published in nine peer-reviewed Kazakhstani journals representing both natural sciences and social sciences. Its main objective is to trace the dynamics of publication activity, identify dominant thematic clusters and research methods, and reveal gaps related to the societal implications of climate change. Methodologically, the research relies on bibliographic and content analysis, classification of articles into thematic categories (water resources, climate change, energy and “green” economy, environmental policy and international cooperation, climate security, and social dimensions), and an examination of keywords and references to major international initiatives. The findings indicate a marked increase in publication output after 2015, which correlates with the Paris Agreement, the expansion of programs by international organizations, and the strengthening of Kazakhstan’s environmental policy framework. The results show that most publications are descriptive or empirical, focusing on legal, environmental, and economic aspects, while genuinely interdisciplinary, predictive, and socially oriented studies remain underrepresented. In particular, there is a lack of research on climate-induced migration, public risk perception, vulnerability of specific social groups, and local adaptation practices. The authors argue for broadening interdisciplinary approaches and for closer integration of climate research with political science, economics, demography, and regional development to support evidence-based climate policy and resilience building in Central Asia. Key words: climate change, water security, Central Asia, scientific publications, sustainable development.